Money Illusion in Charitable Giving in the Absence of Market Price Resistance - Zumaeta, Jorge N. (Journal of Economics and Behavioral Studies, 2021)
Money illusion occurs when individuals fail to differentiate nominal from real values when making financial and economic decisions. As a consequence, they do not adjust their consumption behavior according to real variables. We report an economic experiment to study whether money illusion appears in a very simple setting. It is very important to mention that the experiment was conducted in the context of charitable giving. Our experimental results showed the absence of money illusion among the participants. Our study suggests that money illusion is not present in the absence of price stickiness (market price resistance). This finding supports Shafir et al. (1997). The main objective of our study is to develop a better understanding of economic agents’ charitable giving behaviors as influenced by perceptions of nominal income. Charitable institutions could build fundraising strategies based on behavioral tendencies to the perception of income in nominal or real terms.